Anti-Scar Effects of Micropatterned Hydrogel after Glaucoma Drainage Device Implantation - Yiling Han; Qiangwang Geng; Aimeng Dong; Menglu Jiang; Jingyi Ma; Wulian Song; Pan Fan; Yuanyuan Li; Jiawen Gao; Fenghua Zhang; Jinsong Leng; Huiping Yuan (Research)
Excessive fibrosis is the primary factor for the failure of glaucoma drainage device (GDD) implantation. Thus, strategies to suppress scar formation in GDD implantation are crucial. Although it is known that in implanted medical devices, microscale modification of the implant surface can modulate cell behavior and reduce the incidence of fibrosis, in the field of ophthalmic implants, especially the modification and effects of hydrogel micropatterns have rarely been reported. Here, we designed the patterned gelatin/acrylamide double network hydrogel and developed an innovative GDD with micropattern to suppress inflammatory and fibroblast activation after GDD implantation. Pattern topography suppressed F-actin expression and mitigated actin-dependent nuclear migration of myocardin-related transcription factor A (MRTF-A) during the proliferative phase after GDD implantation. Ultimately, the expression of α-smooth muscle actin (α-SMA), a key fibrosis-related gene product, was suppressed. Moreover, the modified GDD effectively controlled intraocular pressure (IOP), mitigated fibrous formation, and remodeled extracellular matrix (ECM) collagen distribution in vivo. Therefore, the novel GDD with surface patterning interventions provides a promising strategy to inhibit scar formation after GDD implantation and raise the efficacy of GDD implantation.